2012
DOI: 10.5935/1808-8694.20120038
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between nasal resistance and different acoustic rhinometry parameters in children and adolescents with and without allergic rhinitis

Abstract: Our data showed that NR and acoustic rhinometry parameters have negative and significant correlations. Nasal volumes are, in general, better correlated than minimal cross-sectional areas. V5 was the parameter with the highest correlation in the rhinitis group and in the combined analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
(33 reference statements)
0
18
0
1
Order By: Relevance
“…It is noteworthy that TNR and V5 are distinct parameters and that while V5 reflects the geometry of the nasal cavity, TNR is a physiological variable that is measured dynamically during tidal breathing. The differences between these 2 variables were seen clearly in our previous study, where we demonstrated that although significant, the correlation between them was only moderate, with correlation coefficients of around 0.5 [15]. In this preliminary analysis of our data, we compared TNR (obtained by AAR) with several AR parameters (V5, V4, V2-5, and minimal cross-sectional area) at 3 points: baseline, after induction of nasal obstruction, and after administration of a topical decongestant.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is noteworthy that TNR and V5 are distinct parameters and that while V5 reflects the geometry of the nasal cavity, TNR is a physiological variable that is measured dynamically during tidal breathing. The differences between these 2 variables were seen clearly in our previous study, where we demonstrated that although significant, the correlation between them was only moderate, with correlation coefficients of around 0.5 [15]. In this preliminary analysis of our data, we compared TNR (obtained by AAR) with several AR parameters (V5, V4, V2-5, and minimal cross-sectional area) at 3 points: baseline, after induction of nasal obstruction, and after administration of a topical decongestant.…”
Section: Resultsmentioning
confidence: 95%
“…In this preliminary analysis of our data, we compared TNR (obtained by AAR) with several AR parameters (V5, V4, V2-5, and minimal cross-sectional area) at 3 points: baseline, after induction of nasal obstruction, and after administration of a topical decongestant. Since we found that V5 was the parameter with the highest correlation with TNR, we decided to use it in the present study [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been tested in several in vivo studies. Except for one study that reported a strong correlation between mCSA and nasal resistance (Roithmann et al, 1994), all other studies found either a moderate correlation between these variables (typically Pearson ∣r∣ = 0.4 to 0.6) (Scadding et al, 1994; Tai et al, 1998; Wandalsen et al, 2012; Yepes-Nunez et al, 2013), or no correlation at all (Naito et al, 2001; Numminen et al, 2002; Passali et al, 2000; Zhao et al, 2014). To the best of our knowledge, a systematic investigation of the relationship between nasal resistance and mCSA has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The sensitivity and specificity were found to be 32.3% and 70.8%, respectively, in our study. The family and physician's reluctance or hesitation is another disadvantage of this technique; in which case, the lateral cranial x-ray may need to be repeated for correct dose and position.…”
Section: Discussionmentioning
confidence: 66%